Impact of environmental characteristics in urban green spaces on outdoor thermal environment: A case study of Wuhan City, China. Issue 9 (November 2019) - Li, Kun; Liu, Xi; Zhou, Jie
The design of urban spaces could greatly influence the ability of green spaces to improve the thermal environment. Wuhan in the hot-summer and cold-winter zone situated in the central and lower reaches of the Yangtze River in China, has numerous green parks and other natural resources. There is a demand to integrate environmental resources to improve the thermal environment in this city. This research was conducted using multidisciplinary methods including remote sensing inversion, extraction of spatial information, measurement of a multisystem thermal environment index, questionnaires, computational simulations and statistical analysis. By using these methods, the relationship was established between different types of green spaces, urban layouts in different scales and thermal environmental parameters. A multidimensional method for the design of green and urban spaces was developed with the aim to improve the urban thermal environment. The results showed that the relationship among thermal comfort parameters, such as temperature, wind speed and humidity would be influenced by urban layout surfaces and had close relationship with the characteristics of residents' behaviours. The regression models using the physiological equivalent temperature can express the condition of thermal comfort in green spaces quantitatively.